Studies on the robustness of DCC-AB method subject to communication failures - Chen, Yanhong (2019)
With the continuous development of urbanization, urban residents spend most of their time indoors, making the indoor air quality (IAQ) an even more significant issue. The ventilation rate is a critical factor that affects both the IAQ and energy consumption of the heating, ventilation, and air conditioning (HVAC) system. This dissertation mainly focuses on the study of the flow imbalance problem in ventilation systems and identifies the challenges faced by air balancing. An online distributed cooperative control-based air balancing (DCC-AB) method is studied and validated in the experimental platform, and the robustness of this method subject to communication failure is investigated.